How to talk confidently with your child about sex : for parents - Buth, Lenore (Saint Louis, MO : Concordia Pub. House, 2008)
You want your child to know God's plan for his or her sexuality. Buth helps you find the right words to ensure your child has a Christ-centered understanding of one of God's most precious gifts.
Now that I have your attention... -- Marriage today: is it better or worse? -- Children = changes -- Laying a strong foundation in the preschool years -- Six to nine: carpe diem -- Adolescence: on the way -- The teen years: countdown to liftoff -- Young adults: ready to fly.
Includes index.
Keywords: Sex instruction -- Religious aspects -- Christianity